2022
DOI: 10.1186/s12888-022-04030-x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and drunkorexia behaviors among Lebanese adults: the indirect effects of positive and negative metacognition

Abstract: Background Although metacognition processes are a core feature of restrictive eating and alcohol cravings and entail an individual to control both of his/her emotions and thoughts, yet, to our knowledge, a scarcity of research has examined their potential role in drunkorexia as cognitive and emotional predictors. The following study investigates the different associations between two emotion regulation strategies (i.e. emotional suppression and cognitive reappraisal) and drunkorexia behaviors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 92 publications
(160 reference statements)
1
10
0
Order By: Relevance
“…In line with previous studies [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], the present study found that alcohol abuse positively predicted drunkorexia, whereby participants with greater alcohol-related problems exhibited more frequent dysfunctional compensatory behaviors with respect to COVID-19–related variables, the long-term emotional impact of the pandemic also affected drunkorexia behaviors, albeit in a very different way, confirming the uniqueness of this behavior. Specifically, only the frequency of negative intrusive thoughts about the pandemic positively predicted drunkorexia behaviors, while avoidance of these thoughts and the number of COVID-19 negative experiences were not significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous studies [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], the present study found that alcohol abuse positively predicted drunkorexia, whereby participants with greater alcohol-related problems exhibited more frequent dysfunctional compensatory behaviors with respect to COVID-19–related variables, the long-term emotional impact of the pandemic also affected drunkorexia behaviors, albeit in a very different way, confirming the uniqueness of this behavior. Specifically, only the frequency of negative intrusive thoughts about the pandemic positively predicted drunkorexia behaviors, while avoidance of these thoughts and the number of COVID-19 negative experiences were not significant.…”
Section: Discussionsupporting
confidence: 93%
“…Despite recent evidence of the pandemic’s role in contributing to an upsurge in eating disorders, drinking problems, and other negative psychological conditions [ 7 , 12 , 16 , 30 , 40 ], little is known about the impact of pandemic-related stress on drunkorexia behaviors [ 11 ]. However, recent studies have documented an association between drunkorexia, psychological distress, and emotion regulation difficulties [ 56 , 57 , 58 , 59 ]. For instance, Qi and colleagues [ 59 ] observed higher mean scores of affective problems (e.g., anxiety, depression) in young adults engaging in drunkorexia behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…All selected studies had a cross-sectional design. Six studies were conducted in Italy (Casale et al, 2016;Laghi et al, 2018;Mansueto et al, 2022;Palmieri et al, 2023b;Rogier et al, 2022;Spada & Marino, 2017), six studies in Iran (Akbari, 2017;Akbari et al, 2021Akbari et al, , 2023Mazloom et al, 2016;Mohammadkhani et al, 2020;Poormahdy et al, 2022), one study in United Kingdom (Manser et al, 2012), one study in Poland (Dragan, 2015), one in the United States of America (Leahy et al, 2019), one study in Spain (Salguero et al, 2019), one study in Lebanon (Azzi et al, 2022) and one study in Canada (Deleurme et al, 2022).…”
Section: Study Selectionmentioning
confidence: 99%
“…Nine studies were run on non-clinical samples (i.e., university students and general population) (Akbari, 2017, Akbari et al, 2021Akbari et al, 2023;Casale et al, 2016;Deleurme et al, 2022;Manser et al, 2012;Mansueto et al, 2022, study 1;Rogier et al, 2022;Salguero et al, 2019), seven studies on clinical samples (i.e., patients under psychotherapy, outpatients seeking psychological treatment, outpatients with eating disorders, participants with nicotine dependence, alcohol dependence inpatients and drinkers) (Azzi et al, 2022;Dragan, 2015;Leahy et al, 2019;Mansueto et al, 2022, study 2;Ottonello et al, 2019;Palmieri et al, 2023b;Poormahdy et al, 2022), and four studies were run on adolescent samples (Laghi et al, 2018;Mazloom et al, 2016;Mohammadkhani et al, 2020;Spada & Marino, 2017).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation